2010
DOI: 10.1111/j.1537-2995.2009.02531.x
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged elevation of plasma argatroban in a cardiac transplant patient with a suspected history of heparin‐induced thrombocytopenia with thrombosis

Abstract: BACKGROUND: Direct thrombin inhibitors (DTIs) provide an alternative method of anticoagulation for patients with a history of heparin-induced thrombocytopenia (HIT) or HIT with thrombosis (HITT) undergoing cardiopulmonary bypass (CPB). In the following report, a 65-year-old critically ill patient with a suspected history of HITT was administered argatroban for anticoagulation on bypass during heart transplantation. The patient required massive transfusion support (55 units of red blood cells, 42 units of fresh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Respective considerations on HIT prevention have been published in several case reports [27][28][29][30][31][32][33][34][35] and are explicitly discussed in the guidelines published by both the American College of Physicians (ACCP) [12] and the British Society of Hematology [36] . In prospective studies a relevant discrepancy was observed between detection of anti-PF4/heparin antibodies (EIA positive: 27%-50% of the patients) and the capability of these antibodies to activate platelets (SRA or HIPA positive: 7%-40% within the EIA positive patients) [26,37,38] .…”
Section: Heart Transplantationmentioning
confidence: 99%
“…Respective considerations on HIT prevention have been published in several case reports [27][28][29][30][31][32][33][34][35] and are explicitly discussed in the guidelines published by both the American College of Physicians (ACCP) [12] and the British Society of Hematology [36] . In prospective studies a relevant discrepancy was observed between detection of anti-PF4/heparin antibodies (EIA positive: 27%-50% of the patients) and the capability of these antibodies to activate platelets (SRA or HIPA positive: 7%-40% within the EIA positive patients) [26,37,38] .…”
Section: Heart Transplantationmentioning
confidence: 99%
“…The UPLC-MS/MS method was unaffected by factors such as high fibrinogen which can lead to inaccurate determinations of argatroban concentrations by indirect clotting-based methods. Direct measurement of argatroban using a direct approach may provide a more accurate determination of argatroban levels in certain clinical situations known to increase fibrinogen levels, such as in diabetics, post menopausal women, in persons with a high body mass index, and in smokers [18].…”
Section: Resultsmentioning
confidence: 99%
“…Because there are no reversal agents for DTIs, elevated levels of these drugs carry the risk of life-threatening bleeding complications [16]. Thus, underestimation of argatroban may exacerbate certain clinical situations and lead to extended coagulopathy [18]. The direct UPLC-MS/MS assay was unaffected by elevated fibrinogen levels and thus, should provide a more accurate determination of argatroban concentrations in patients with abnormally high fibrinogen levels (Fig.…”
Section: Methods Comparisonmentioning
confidence: 97%
“…The liver metabolizes argatroban. Genzen and colleagues reported that a cardiac transplant patient with a suspected history of HIT had excessive anticoagulation and blood loss in the perioperative period when argatroban was used because the prolonged elevation of argatroban concentration after infusion may have been influenced by the patient's critical condition, cardiac output, and decreased postoperative hepatic function [8]. Therefore, in our patients, the anticoagulation effect of argatroban was prolonged, probably because of liver dysfunction accompanied by right-sided heart failure, leading to abnormality in haemostasis.…”
Section: Discussionmentioning
confidence: 99%